Analysis Of The Socio-Economic Effect On Unemployment In Gorontalo Province - Ivan Santoso; Muhamad Zikri Zam-Zam; Syarwani Canon (Jurnal Ekonomi Pembangunan, 2022)
This study aims to know whether or not socio-economic indicators affect unemployment in Gorontalo Province. This study uses secondary data from 5 regencies and one city (Gorontalo Regency, Bone Bolango Regency, Gorontalo Utara Regency, Baalemo Regency, Pohuwato Regency, and Gorontalo City) from 2011 to 2020 sourced from journals, articles, and government agencies, such as Statistics of Indonesia. The data analysis technique uses panel data regression analysis. The finding shows that population growth has a negative and insignificant effect on unemployment in Gorontalo Province. Population growth will not necessarily reduce the unemployment rate in the Regencies/cities in Gorontalo Province. Economic growth has a negative and significant effect on unemployment in Gorontalo Province; every increase in economic growth can reduce the unemployment rate in the Regencies/cities in Gorontalo Province. Inflation has a negative and insignificant effect on unemployment in Gorontalo Province; inflation does not necessarily reduce the unemployment rate in the Regencies/cities in Gorontalo Province. The Human Development Index has a negative and significant effect on unemployment; This means that the increase in the human development index can reduce the unemployment rate in the Regency/City in Gorontalo Province.